Diabetic ketoacidosis and hyperglycemic hyperosmolar state are associated with higher in-hospital mortality and morbidity in diabetes patients hospitalized with ST-elevation myocardial infarction, but not within 30 days of readmission - Turki Almutairi; Soha Dargham; Amin Jayyousi; Jassim Al Suwaidi; Charbel Abi Khalil (PLoS ONE, 2025)
Background While the cardiovascular risk of hyperglycemia has been thoroughly elucidated in patients with type 2 diabetes (T2DM) hospitalized for myocardial infarction, the evidence surrounding acute severe hyperglycemia is less well-established. Our study aimed to explore the impact of diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS), both severe hyperglycemic conditions, on cardiovascular outcomes in patients with T2D admitted for ST-elevation myocardial infarction (STEMI). Methods We used the National Readmission Database (2016–2019) to extract patients with T2DM and STEMI at baseline. Subsequently, we selected cases of DKA and HHS. The primary endpoint was in-hospital mortality. Secondary endpoints included in-hospital acute renal failure, cardiogenic shock, and 30-day readmission and mortality. Results The presence of DKA increased the adjusted odds of mortality and cardiogenic shock by almost 2-fold (adjusted Odds Ratios aOR = 2.30 [1.70–3.12], 2.055 [1.602–2.637], respectively) and renal failure by nearly 5-fold (aOR = 5.175 [4.090–6.546]). HHS was also associated with higher odds of mortality, acute renal failure, and cardiogenic shock. In 30 days, DKA and HHS increased the risk of readmission (aOR = 1.815 [1.449–2.75], 1.751 [1.376–2.228], respectively). There were no differences in the rates of cardiovascular disease, mortality, or other cardiovascular events between DKA and HHS patients. Within 30 days of readmission, DKA and HHS were associated with higher odds of readmission but not mortality. Cardiovascular disease was the most common etiology of readmission in all patients. The incidence of non-STEMI was the highest in DKA patients, and the incidence of STEMI was the highest in the HHS group. Conclusion The presence of diabetic ketoacidosis or hyperglycemic hyperosmolar state is associated with higher odds of mortality, renal failure, cardiogenic shock, and 30-day readmission in STEMI patients with type 2 diabetes, highlighting the need for enhanced clinical management and monitoring of patients experiencing acute hyperglycemia.